“Calling Bullshit on the Whole Thing”: Women, Health, Agency and Maternity in the Popular Film, What to Expect When You’re Expecting - Hill, Nicole (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
Popular culture is a significant site of discourse on maternity, in the maintenance of hegemonic ideologies and practices relating to maternity, and in the silencing of alternatives to commonly accepted norms of maternity. This essay examines the social and political issues of pregnancy and birth as presented in What to Expect When You’re Expecting (Jones) and engages in a critical feminist analysis of the film in terms of maternity and the Women’s Health Movement (whm). Gender-based oppression, authoritative medicine, and individualized and essentialized reproduction are discussed as they appear in the film and in women’s health discourse. This essay argues that the film supports dominant ideologies of maternity and even manipulates the terms of feminist health care to create the appearance of support for more alternative or even oppositional representations; thus, allowing the film to limit the progress of the whm while simultaneously appearing to support it. As the whm aims to reclaim women’s subjectivity, their agency, and their epistemic power, cultural studies can be employed to foster oppositional decodings of the film, encouraging viewers to question the content of the film and its support of hegemonic values